Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set: 108

Answer

$4x^{2}+4x+1$

Work Step by Step

We are given the expression $(2x+1)^{2}$, which is equivalent to $(2x+1)(2x+1)$. We can use the FOIL method to simplify. F=$2x\times 2x=4x^{2}$ O= $2x\times1=2x$ I=$1\times 2x=2x$ L=$1\times1=1$ Now, we can add these terms together. $(2x+1)^{2}=(4x^{2})+(2x)+(2x)+(1)=4x^{2}+4x+1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.